Wireless and satellite systems : 8th International Conference, WiSATS 2016, Cardiff, UK, September 19-20, 2016, Proceedings /: 8th International Conference, WiSATS 2016, Cardiff, UK, September 19-20, 2016, Proceedings. (2017) - Unknown
No abstract available